과학영재들이 문제발견 과정에서 나타내는 과학개념 연결방식과 융합적 사고의 특징 - 박미진; Mi-jin Park; 서혜애; Hae-ae Seo (과학교육연구지, 2018)
본 연구는 과학영재들이 문제발견 과정에서 나타내는 과학개념 연결방식과 융합적 사고의 특징을 분석하는데 목적을 두었다. 이를 위해 2015학년도 광역시 소재 대학부설 과학영재교육원 중등 심화과정 전공영역별로 지원한 228명을 모집단으로 설정하고, 연구대상은 선발과정 1차전형에서 실시한 과학 창의적 문제해결력 검사도구 점수를 기준으로 상위 30%에 속하는 67명을 상위집단으로, 하위 30%에 속하는 64명을 하위집단으로 구분하고, 두 집단에 속하는 총131명을 표집하였다. 자료수집을 위한 검사도구 문항은 초등과학 교육과정에서 추출한 소리, 전기, 무게, 온도, 호흡, 광합성, 날씨, 지진의 과학개념 8개를 활용하여 개발하였다. 검사문항은 과학개념 8개 가운데 가장 선호하는 과학개념 2개를 연결하여 과학적 질문을 생성하도록 제시하였으며, 연구대상이 진술한 과학적 질문을 분석하였다. 연구결과 과학영재들은 심화과정 전공영역에 따라 과학개념 연결 선호도에서 차이를 나타냈다. 과학적 질문에서 나타난 과학개념 연결방식의 특징을 분석하기 위해 수집한 자료를 먼저관계, 유사성, 비유사성에 근거한 연결방식으로 분류하였다. 나아가 관계에 근거한 과학개념 연결방식은 속성, 수단, 영향, 예측, 원인, 측정, 현상으로, 유사성에 근거한 과학개념 연결방식은 속성, 대상, 과학적 원리, 현상에 근거한 연결로, 비유사성에 근거한 과학개념 연결방식은 병렬, 자원, 제거에 근거한 연결로 세분화하였다. 상위집단과 하위집단 간에 과학개념 연결방식은 통계적으로 유의미한 (p <.000) 차이를 보였다. 상위집단은 하위집단에 비해 서로 다른 과학영역에 해당하는 개념을 연결하여 과학적 질문을 더 많이 생성하였으나, 하위집단은 상위집단에 비해 동일한 과학영역 내 개념들을 연결하여 과학적 질문을 더 많이 생성하였다. 상위집단은 하위집단에 비해 유사성에 근거한 과학개념 연결방식을 더 빈번하게 사용하는 특징을 나타낸 반면, 하위집단은 상위집단에 비해 비유사성에 근거하여 단순하게 병렬시키는 연결을 더 빈번하게 사용하는 것으로 나타났다. The study aimed to investigate how the science gifted connect and integrate science concepts in the process of problem finding. Research subject was sampled from 228 applicants for a science gifted education center affiliated with a university in 2015. A creative problem solving test (CPST) in science, which administered as an admission process, was utilized as a reference to sample two groups. Sixty-seven students from top 30% in test scores were selected for the upper group and 64 students from bottom 30% in test scores were selected for the lower group. The CPST, which was developed by researchers, included one item about how to connect two science concepts among eight science concepts, sound, electricity, weight, temperature, respiration, photosynthesis, weather, and earthquake extracted from elementary science curriculum. As results, there were differences in choosing two concepts among four science major areas. The ways of connecting science concepts were characterized by three categories, relation-based, similarity-based, and dissimilarity-based. In addition, relation-based was characterized by attributes, means, influences, predictions, and causes; similarity-based was by attributes, objects, scientific principles, and phenomena, and dissimilarity-based was by parallel, resource, and deletion. There were significant (p <.000) differences in ways of connecting science concepts between the upper and the lower groups. The upper group students preferred connecting science concepts of inter-science subjects while the lower group students preferred connecting science concepts of intra-science subject. The upper group students showed a tendency to connect the science concepts based on similarity. In contrast, the lower group students frequently showed ways of connecting the science concepts based on dissimilarity. In particular, they simply parallelled science concepts.